ANALISIS PENGARUH DUKUNGAN PIMPINAN DAN DUKUNGAN ORGANISASI PADA KINERJA DAN KOMITMEN AFEKTIF KARYAWAN PT INKA MADIUN - Lusdiyanti, Evi Siwi (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
The purposes of this study were (1) analyze and test the effect of leadership support to the organization support in the PT INKA Madiun (2) analyze and test the effect of leadership support on affective commitment of employees of PT INKA Madiun, (3) analyze and test the effect of leadership support on performance employees of PT INKA Madiun, (4) analyze and test the effect of organizational support on employee affective commitment PT INKA, and (5) analyze and test the effect of organizational support on the performance of employees of PT INKA. Population in this research are PT INKA Madiun employees. The samples were 200 respondents with stratified random sampling technique sampling. Hypothesis testing using Structural Equation Modeling (SEM). The results of analysis of research data analysis support the influence of the leadership and support organization in the performance of employee affective commitment dam PT INKA Madiun was concluded: (1) leadership support positive effect on organizational support in PT INKA Madiun (2) support the leadership did not affect employee affective commitment PT INKA Madiun, (3) support the leadership does not affect the performance of employees of PT INKA Madiun, (4) organizational support has positive influence on employee affective commitment PT INKA, (5) organizational support positive effect on employee performance of PT INKA, (6) organizational support mediate the effect of leadership support on affective commitment of employees of PT INKA Madiun, (7) organizational support mediate the effect of leader support on the performance of employees of PT INKA Madiun